Pengaruh Profitabilitas, Leverage, Kinerja Lingkungan, Dan Corporate Governance Terhadap Pengungkapan Emisi Karbon - Winata, Octavia Audrey; Wirajaya, I Gde Ary (CV. Ulil Albab Corp, 2025)
Climate change triggered by carbon emissions has become a global concern due to its serious impacts on ecosystems, health, and the economy. The Indonesian government has set a target of Net Zero Emissions by 2050 for 8 energy-intensive subsectors, one of which is the food and beverage subsector, consuming 18.5% of energy. This study aims to analyze the influence of profitability, leverage, environmental performance, and corporate governance on carbon emission disclosure in the food and beverage subsector companies listed on the Indonesia Stock Exchange for the period of 2021-2023. The sample determination method used in this study is purposive sampling. The sample used consists of 14 companies, with data processing methods employing multiple linear regression analysis. The results of this study show that environmental performance, the board of commissioners, and independent commissioners have a positive influence on carbon emission disclosure, while profitability, leverage, and the audit committee have no influence on carbon emission disclosure.